Publisher Correction: Population scale data reveals the antidepressant effects of ketamine and other therapeutics approved for non-psychiatric indications - Isaac V. Cohen (Nature Portfolio, 2017)
A correction to this article has been published and is linked from the HTML version of this paper. The error has not been fixed in the paper.